Parallel computational fluid dynamics : towards teraflops, optimization, and novel formulations : proceedings of the Parallel CFD '99 Conference /: towards teraflops, optimization, and novel formulations : proceedings of the Parallel CFD '99 Conference. (2000) - Unknown
No abstract available